Functional Gel Poly-m-phenyleneisophthalamide Nanofiber Separator Modified by Starch to Suppress Lithium Polysulfides and Facilitate Transportation of Lithium Ions for High-Performance Lithium-Sulfur Battery. Issue 7 (1st July 2021) - Yang, Qi; Yan, Chenzheng; Wang, Xiaoxiao; Xiang, Hengying; Chen, Junyan; Wang, Gang; Wei, Liying; Cheng, Bowen; Deng, Nanping; Zhao, Yixia; Kang, Weimin
Abstract : A functionally fluorinated emulsion and starch particles co-doped electrospun poly-m-phenyleneisophthalamide (PMIA) nanofiber membrane-based gel polymer electrolyte was produced to inhibit the "shuttle effect" of lithium polysulfides (LiPSs) and promote the transport of lithium ions for lithium-sulfur (Li-S) batteries. The high mechanical property, high thermal stability, and significant preserving liquid electrolyte of the prepared membrane are derived from the addition of functionally fluorinated emulsion and starch particles. Specially, with the chemical adsorption of –OH in starch particles and physical prevention of a gel state deriving from the prepared membrane, the lithium polysulfides are effectively controlled in the side of the cathode. In addition, the polar group and stable helix structure existing in starch particles are beneficial to the fast migration of Li + . Therefore, the battery with the Starch-F PMIA separator possesses a first-discharge capacity of 1117.8 mAh g −1 at 0.5 C. Moreover, an Li-S battery assembled with the prepared membrane also reflects preeminent rate performance, low interface impedance, and admirable cycling stability. In consequence, the Starch-F PMIA separator is a promising candidate for the progressive lithium sulfur batteries.